2019
DOI: 10.3390/jcm8050732
|View full text |Cite
|
Sign up to set email alerts
|

Substance Abuse and Male Hypogonadism

Abstract: Progressive deterioration of male reproductive function is occurring in Western countries. Environmental factors and unhealthy lifestyles have been implicated in the decline of testosterone levels and sperm production observed in the last fifty years. Among unhealthy lifestyles, substance and drug abuse is a recognized cause of possible alterations of steroidogenesis and spermatogenesis. Alcohol, opioids and anabolic-androgenic steroids are capable to reduce testosterone production in male interfering with tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 148 publications
(283 reference statements)
2
49
0
Order By: Relevance
“…As far the clinical aspects, childhood cancer [4], pediatric varicocele [5], and risky lifestyles [6] (including substance abuse [7]) are addressed in the current Special Issue. Duca et al […] evaluate the testicular function of childhood cancer survivors and address which cancer, therapy, and age of treatment has the worst reproductive outcomes in adulthood.…”
mentioning
confidence: 99%
“…As far the clinical aspects, childhood cancer [4], pediatric varicocele [5], and risky lifestyles [6] (including substance abuse [7]) are addressed in the current Special Issue. Duca et al […] evaluate the testicular function of childhood cancer survivors and address which cancer, therapy, and age of treatment has the worst reproductive outcomes in adulthood.…”
mentioning
confidence: 99%
“…Case reports, as well as animal studies, showed that spontaneous recovery of spermatogenesis could occur after 10-12 weeks of alcohol withdrawal, equivalent to one cycle of spermatogenesis [95,96]. Besides its adverse effect on spermatogenesis, alcohol has also been shown to decrease testosterone blood concentration by acting both on testicular and central (hypothalamic and pituitary) levels [97]. Indeed, alcohol was shown to exert an inhibitory action on the enzymes that catalyze the conversion of pregnenolone to progesterone and androstenedione to testosterone (3 β-hydroxysteroid dehydrogenase and 17-ketosteroid reductase, respectively) [98].…”
Section: Alcoholmentioning
confidence: 99%
“…In this commentary, I propose that inhibition of testosterone production by opioids may contribute to the pathophysiology of suicidal behaviour among male opioid users. The inhibitory impacts of opioid substances on the hypothalamic-pituitary-gonadal axis have been recognized for several decades (Duca et al, 2019). All opioids reduce testosterone production because they hamper secretion of hypothalamic gonadotropin-releasing hormone and disrupt its normal pulsatility (Duca et al, 2019).…”
Section: Declaration Of Conflicting Interestsmentioning
confidence: 99%
“…The inhibitory impacts of opioid substances on the hypothalamic-pituitary-gonadal axis have been recognized for several decades (Duca et al, 2019). All opioids reduce testosterone production because they hamper secretion of hypothalamic gonadotropin-releasing hormone and disrupt its normal pulsatility (Duca et al, 2019). Opioid use decreases levels of testosterone in men regardless of the route of administration (Duca et al, 2019).…”
Section: Declaration Of Conflicting Interestsmentioning
confidence: 99%